ANALISIS WACANA KRITIS TEUN VAN DIJK DALAM CERPEN “TUKANG DONGENG” KARYA KEN HANGGARA - Jumriah,, Andi Saadillah, Nuruh H, (LP2M IAIN Ambon, 2020)
Abstract In the analysis of critical discourse, discourse is not only understood as a study of language. Language is analyzed not only from the linguistic aspect, but also relates it to context. This study examines the literary text, especially the short story written by Ken Hanggara